Bentuk Tafsir Dalam Kajian Alquran - Desi Lestari; Abu Anwar; Zainur (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2022)
Interpretation through interpretation is a human effort to explore his highest ability in understanding a verse so that he can understand well what is meant by Allah ta'ala verse. The effort is not easy, indeed, because every word written or spoken is only well understood by the owner. Thus, the truth that results from any interpretation is not absolute. For this purpose, the interpreter of the Qur'an takes a certain methodology to interpret it, especially in determining the source or reference to be used for interpretation. The diversity of these forms can be seen from the resulting interpretation. Sources and forms of interpretation developed along with the periodization of Muslims in understanding the Qur'an, starting from the first period from the time of the Prophet Muhammad, companions, and tabiin. Then continued the second period after tabi'n.